2016
DOI: 10.18352/ijc.743
|View full text |Cite
|
Sign up to set email alerts
|

New rules are not rules: Privatization of pastoral commons and local attempts at curtailment in southwest Madagascar

Abstract: This paper examines the case of indigenous privatization of the important fodder tree samata (Euphorbia stenoclada) and concurrent legal curtailment of this privatization among the Tanalana people of southwest Madagascar from a long-term perspective. Applying a framework for institutional change to empirical data derived from interviews conducted in 20 villages in the Mahafaly Plateau region, the study explores the process and mechanisms involved in creating and asserting private property rights to this common… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 27 publications
0
7
0
4
Order By: Relevance
“…If conservationists are interested in supporting collective action for sustainable resource management on local levels, they have to be aware of long periods of rule negotiation (Berkes 2004, Goetter andNeudert 2016). Even when the moment of establishing a rule arrives, it is important to remember that existing rules are constantly being renegotiated.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…If conservationists are interested in supporting collective action for sustainable resource management on local levels, they have to be aware of long periods of rule negotiation (Berkes 2004, Goetter andNeudert 2016). Even when the moment of establishing a rule arrives, it is important to remember that existing rules are constantly being renegotiated.…”
Section: Resultsmentioning
confidence: 99%
“…It is difficult to find the right form of agreements for CBM and also to identify the right level to anchor the CBM association. Each level is problematic in different ways : (i) A COBA association consisting of voluntary members of one or more fokontany (Model Ia and b), excludes other resource users (Pollini and Lassoie 2011), (ii) a CO-BA association consisting of all people in a fokontany (fokontanyfokonolona) (Model II) contradicts the trans-fokontany resource use philosophy (Goetter and Neudert 2016), and (iii) a COBA association on the commune or clan level (Modell III) is not action orientating for the local people in their daily behaviour (Kull 2002, Blanc-Pamard andFauroux 2004). The optimal solution would be to establish a dina on the commune and fokontany level based on a rule of ancestor or taboo that includes at least all Tanalana clans and is reinforced annually by a titike that obliges other ethnic groups to follow the agreement.…”
Section: Resultsmentioning
confidence: 99%
“…Some differences undoubtedly remain, but to a greater or lesser extent, all the papers share these basic features. Although Goetter and Neudert certainly depart from the strong historical flavour of the other three papers, their study of institutional change in the pastoral communities of southwest Madagascar does come right to the centre of the motivation of the workshop and this special issue (Goetter and Neudert 2016). In close relation with this, the third and last feature linking together all the articles relates to their attention to often neglected topics in the commons literature -most notably institutional change.…”
Section: Overview Of Articlesmentioning
confidence: 95%
“…In contrast with the relative success exhibited by the cases analysed by Bonan and De Moor et al, the articles by Goetter and Neudert (2016) and Largo-Jiménez (2016) explore the inability of certain collective institutions to satisfactorily respond to the challenges they face over time. In their analysis of privatisation of pasture lands in Madagascar, Goetter and Neudert flesh out much of the 'tragedy of the commons' as originally (and often wrongly) depicted by Hardin in his seminal 1968 paper: the inevitable transformation of an open-access situation into a new governance regime where private property rights prevail at the expense of alternative community-based arrangements.…”
Section: Overview Of Articlesmentioning
confidence: 95%
“…However, the over-exploitation of natural stands of this species has become a growing problem. Goetter et al [41] showed that improper cutting can damage or even kill silver thicket plants that meanwhile show a mortality rate of about 13–22%, particularly within and around villages. Hence, recommendations that were intended to be communicated through comics considered a cutting only at the branch level (Fig 2B) without damage to the trunk or apical meristems while ensuring sufficient time between harvest events for tree regeneration [42].…”
Section: Methodsmentioning
confidence: 99%